Respostas da mamona à irrigação e à aplicação de potássio em argissolo vermelho-amarelo - Nobre, Jefferson Gonçalves Américo (2007)
The objective of this work was to evaluate the vari ables of production of the castor bean, variety IAC Guarani, under different levels o f irrigation and increases levels of potassium fertilization, applied through fertirriga tion. As a consequence, three different works, denominated of 1, 2 and 3, they were implanted in an experimental area of the Federal University of Ceará, in Fortale za (03°44'S, 38°33'W, 19,5 m). The experimental maping of the three experiments was in blocks at random, with five treatments and four repetitions, defined in functio n of the level of irrigation (1 and 2) and of the level of potassium fertilization (3). In the experiments 1 and 2, the treatments corresponded to 25; 50; 75; 100 and 125% of the evaporation measured by evaporimeter reduced tank (EVAr) and 35; 70; 105 ; 140 and 175% of the evaporation measured in the Piche evaporimeter (EPi), respectively. In the experiment 3, the treatments were defined in function of the potassium fertilization: 0; 50; 100; 150 and 200% of the recommendation of the soil analysis. In all, they were following variables were appraised: size of the rac emo of 1st order, number of fruits, weight of 100 seeds, productivity of the racemes (1 ª, 2ª and 3ª orders) and total productivity. It was verified that the castor bean answered in productivity to the application of water and the potassium fertirrigati on, arriving to maximum values of productivity of 4.161; 4.010 and 3.341 kg ha -1 in the experiments 1; 2 and 3, respectively. In the experiment 1, it was ended tha t the use for the producing of larger irrigation sheets increases to a certain value limi ts the weight of 100 seeds for racemes of 2ª and 3ª orders and the productivity, f rom which these variables start to decrease; the reduced tank was efficient to esteem the water requirements of the castor bean. In the experiment 2, the use for the p roducing of larger irrigation sheets increases to a certain value limits the productivit y for raceme of 2ª and 3ª orders and positive way about the productivity of the castor bean.